Bridging the Mobile Digital Divide in Sub-Saharan Africa : Costing under Demographic Change and Urbanization - Alper, Emre (IMF Working Papers; Working Paper ;, 2019)
Digital connectivity, including through the modern cellular network technologies, is expected to play a key role for the Future of Work in sub-Saharan Africa (SSA). We estimate the cost of introducing a full-scale 4G network by 2025 in SSA and an operable 5G network by 2040. We adapt the costing model of Lombardo (2019) by accounting for the significant demographic transformation and rapid urbanization in SSA. We use the WorldPop and GADM databases and the UN's medium-variant population projections to project the population densities at the highest level of administrative division for each SSA country in 2025 and 2040. For full 4G connectivity, the required capital and operational costs stands approximately at USD 14 billion by 2025 and for 5G connectivity, costs amount to USD 57 billion in 2040, conditional on having the 4G in place by 2025. These costs roughly translate to 8.4 percent of annual subscriber income, on a median basis, by 2025 for 4G and 4.9 percent of subscriber income by 2040 for 5G. Having the infrastructure in place is not sufficient to bridge the mobile Digital Divide. In addition, policies are needed to address affordability and knowledge gaps.